2019
DOI: 10.1371/journal.pone.0223806
|View full text |Cite
|
Sign up to set email alerts
|

Early and long-term outcomes of coronary artery bypass surgery with and without use of heart-lung machine and with special respect to renal function - A retrospective study

Abstract: The aim of our study was to compare early and long-term outcome of patients undergoing either on-pump or off-pump coronary artery bypass grafting with special focus on impairment of renal function. Five hundred ninety-three consecutive patients undergoing coronary artery bypass grafting were retrospectively analyzed. They were assigned either to on-pump (n = 281) or to off-pump (n = 312) group. Early and long-term outcomes were analyzed with special focus on renal function. Basic demographics and preoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…The off-pump method of surgical procedures described in our analysis allowed us to minimalize the influence of post-operative inflammatory response on our results. Several studies confirmed that the off-pump surgical revascularization technique omits the risk for inflammatory activation secondary to CBP administration [ 40 43 ]. In the Mirhafez et al [ 41 ] study serum cytokines levels in off-pump coronary surgery were lower compared with on-pump method.…”
Section: Discussionmentioning
confidence: 99%
“…The off-pump method of surgical procedures described in our analysis allowed us to minimalize the influence of post-operative inflammatory response on our results. Several studies confirmed that the off-pump surgical revascularization technique omits the risk for inflammatory activation secondary to CBP administration [ 40 43 ]. In the Mirhafez et al [ 41 ] study serum cytokines levels in off-pump coronary surgery were lower compared with on-pump method.…”
Section: Discussionmentioning
confidence: 99%
“…Dealing with RCC and TT either below or above the diaphragm forced us to think how to resect them without using CBP ( 9 , 10 ). The goal was to avoid sternotomy and complications related to CPB ( 11 ). Redo sternotomy due to prior CABG is technically challenging, because of increased risk of adhesions and injury to critical structures ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23] Over the last two decades, many studies have been dedicated to proving the safety of these strategies by comparing them with conventional ONCAB. [23][24][25][26][27][28][29] Few studies directly compared the effectiveness of CABG surgery under off-pump, ON-BH and MiECC to power for convincing clinical benefits in short-term and longterm outcomes of these three interventions. Network meta-analysis (NMA), as an extension of pairwise metaanalysis, allows the evaluation of multiple treatments in a single analysis.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Over the last two decades, many studies have been dedicated to proving the safety of these strategies by comparing them with conventional ONCAB 23–29. Few studies directly compared the effectiveness of CABG surgery under off-pump, ON-BH and MiECC to power for convincing clinical benefits in short-term and long-term outcomes of these three interventions.…”
Section: Introductionmentioning
confidence: 99%